Erratum to “Field of Study, Earnings, and Self-Selection” - Kirkeboen, Lars; Leuven, Edwin; Mogstad, Magne (Quarterly Journal of Economics, 2017)
This erratum corrects an omission in the published version of the paper appearing in the August 2016 issue of The Quarterly Journal of Economics (vol. 131, no. 3). Figures XI and XII were omitted in error from the printed manuscript. They are reproduced below. Estimated Payoffs to Largest Institutions Graph shows the 2SLS payoff estimates (estimate and CI’s) of the 10 largest institutions (those with at least 1000 applicants completing in our sample). All payoffs are relative to the Universeity of Oslo (UiO). Completed institutions are instrumented with predicted institution. Payoffs to fields are instrumented using predicted field. In addition to our baseline controls, the specification includes controls for preferred and next-best field and institution. Testable Implication of Sorting Based on Comparative Advantage This figure graphs the distribution of the differences in relative payoffs to field j versus k between individuals whose preferred field is j and next-best alternative is k and those with the reverse ranking. To construct this graph, we use the complier weighted distribution of estimates in Online Appendix Table B.VI.